The Cistercian monastery of Zaraka, Greece - Campbell, Sheila D. (Monastic life, 2018)
Overview of the site, daily life, and small finds / Sheila Campbell -- Reconstructing the abbey library of Zaraka / Diane Reilly -- Zaraka : the human remains / Sandra Garvie-Lok